Characterization of cultured cholangiocytes isolated from livers of patients with primary sclerosing cholangitis - Tabibian, James H. (2014)
Primary sclerosing cholangitis (PSC) is a chronic, idiopathic cholangiopathy. The role of biliary epithelial cells, i.e. cholangiocytes, in PSC pathogenesis is unknown and remains an active area of research. Here, through cellular, molecular, and next-generation sequencing (NGS) methods, we characterize and identify phenotypic and signaling features of isolated PSC patient-derived cholangiocytes. We isolated cholangiocytes from stage 4 PSC patient liver explants by dissection, differential filtration, and immune-magnetic bead separation. We maintained cholangiocytes in culture and assessed for: i) cholangiocyte, cell adhesion, and inflammatory markers; ii) proliferation rate; iii) transepithelial electrical resistance (TEER); iv) cellular senescence; and v) transcriptomic profiles by NGS. We used two well-established normal human cholangiocyte cell lines (H69 and NHC) as controls. Isolated PSC cells expressed cholangiocyte (e.g. cytokeratin 7 and 19) and epithelial cell adhesion markers (EPCAM, ICAM) and were negative for hepatocyte and myofibroblast markers (albumin, α-actin). Proliferation rate was lower for PSC compared to normal cholangiocytes (4 vs. 2 days, respectively, p<0.01). Maximum TEER was also lower in PSC compared to normal cholangiocytes (100 vs. 145 Ωcm(2), p<0.05). IL-6 and IL-8 (protein and mRNA) were both increased compared to NHCs and H69s (all p<0.01). The proportion of cholangiocytes staining positive for senescence-associated β-galactosidase was higher in PSC cholangiocytes compared to NHCs (48% vs. 5%, p<0.01). Lastly, NGS confirmed cholangiocyte marker expression in isolated PSC cholangiocytes and extended our findings regarding pro-inflammatory and senescence-associated signaling. In conclusion, we have demonstrated that high-purity cholangiocytes can be isolated from human PSC liver and grown in primary culture. Isolated PSC cholangiocytes exhibit a phenotype that may reflect their in vivo contribution to disease and serve as a vital tool for in vitro investigation of biliary pathobiology and identification of new therapeutic targets in PSC.